Vaccinated Healthcare Workers’ Adherence to COVID-19 Prevention Measures and Associated Factors in Northwest Ethiopia: A Facility-Based Cross-Sectional Study - Gubae K; Agegnew Wondm S; Birhane W; Fetene A; Arega Moges T; Kiflu M (Dove Medical Press, 2022)
Kale Gubae,1 Samuel Agegnew Wondm,1 Worku Birhane,1 Akalu Fetene,1 Tilaye Arega Moges,2 Mekdes Kiflu1 1Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Pharmacy, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Kale Gubae, Email kalegubae1@gmail.comBackground: The initial response to coronavirus disease 2019 (COVID-19) was non-pharmaceutical interventions (NPIs). Long-term protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection does not appear to be possible by either infection or vaccination. Thus, traditional herd immunity seems impossible. In addition to increasing vaccination rates, NPIs may be needed.Methods: A facility-based cross-sectional study was conducted among vaccinated healthcare workers. The study took place from July 15 to August 15, 2022. A self-administered questionnaire was used for data collection. In a multivariable logistic regression model, a p-value of less than 0.05 was considered statistically significant.Results: Four hundred eleven healthcare workers were included in the study. Sixty percent of participants were fully vaccinated. After vaccination, 10.2% of respondents reported infection with SARS-CoV-2. The study showed that 49.4% of participants had a good knowledge of the efficacy and safety of vaccines against SARS-CoV-2. In this study, 36% of individuals adhered well to the COVID-19 prevention strategies. Good knowledge of the efficacy and safety of SARS-CoV-2 vaccines (AOR = 1.69, 95% CI: 1.03- 2.78) increased the odds of implementing preventive measures. Healthcare workers who perceived a low and medium risk of SARS-CoV-2 infection after vaccination and who were knowledgeable about SARS-CoV-2 breakthrough infections were less likely to follow preventive measures.Conclusion: The knowledge of healthcare workers regarding the efficacy and safety of vaccines against SARS-CoV-2 was comparable. However, a large proportion of healthcare workers poorly adhered to prevention practices. Therefore, to reduce the risk of SARS-CoV-2 infection among healthcare professionals, prevention strategies must be continuously evaluated and awareness of the need for preventive measures must be raised even after vaccination.Keywords: prevention practices, vaccine, knowledge, Ethiopia